Ice-out - Casanova, Mary (University of Minnesota Press, 2016)
In 1920s Minnesota, life is hard for nineteen-year-old Owen Jensen and his family after their father dies but gets considerably worse when Owen becomes involved in the deaths of a sheriff and deputy.